Upaya Guru SKI dalam Meningkatkan Minat Belajar Siswa Di MA NW Penendem - Muhamad Zaril Gapari; Ahmad Izzudin; Hesty Muliana (Pendidikan Al-Gafari, 2024)
Education aims to shape character regarding religion, personality, intelligence and so on. To achieve this goal cannot be separated from the role of an educator or teacher. The purpose of this researchis to determine the effort of SKI teachers in increasing students’ interest in learning MA NW Penendem and to find out the supporting and inhibiting factor for students’ interest in learningat MA NW Penendem. This research uses a qualitative approach in the form of descriptive. The method used in collecting data are the observation method, interview method and documentation method The results that can be seen from the SKI teacher’sefforts in increasing students’ interest in learning MA NW Penendem include several strategies involving approaches to students, classroom management, use of varied methods, constructive evaluation and punishment Factors supporting students’ interest in learning MA NW Penendem includes teacher mastery of teaching materials, student interest, SKI learning schedule in the morning, adequate facilities and infrastructure and good teacher teaching experience. Meanwhile, inhibiting factors for students’ interest in learning MA NW Penendem include limited class hours, SKI learning time in the last hour, and limited understanding of technology by teachers.